Optimalisasi Peran Guru Bimbingan dan Konseling dalam Implementasi Pembelajaran Deep learning untuk Mengembangkan Potensi Generasi Z - Rakhmawati, Dini; Yulienjatiningsih, Yovitha; Suyati, Tri (Pelita: Jurnal Pengabdian kepada Masyarakat, 2025)
Generation Z, with unique characteristics and different learning needs, requires innovative and relevant learning approaches. Deep learning as a learning method that emphasizes deep understanding and application of knowledge, offers great potential to meet these needs. However, the implementation of deep learning in schools in Indonesia still faces various obstacles. One of the main ones is the lack of understanding and skills of BK teachers in applying this approach. The method of implementing the community service program This service activity is carried out for 2 weeks which is divided into three stages, namely: (1) planning stage, (2) implementation stage, (3) evaluation stage. Participants showed a good level of understanding of the basic concepts and potential applications of deep learning in an educational context, with an average comprehension score of 88. This indicates that this activity has succeeded in achieving one of its goals, which is to provide basic knowledge about deep learning.